SYNERGISTIC EFFECT OF FRUITS EXTRACTS OF Balanites aeqyptiaca AND Adansonia digitata ON LIPIDERMIC PARAMETERS OF DIABETICS ALBINO RAT - Gabi, Baba; Umar, Hauwa; Haruna, Hauwa; Ado, Aminu (FUDMA JOURNAL OF SCIENCES, 2023)
Lipidemia is a significant risk factor for cardiovascular disease, particularly in people with diabetes mellitus. High plasma triglyceride concentration, low HDL cholesterol concentration, and elevated concentration of tiny dense LDL cholesterol particles are some of its distinguishing features. Fruits from Balanites aeqyptiaca and Adansonia digitata have the ability to decrease blood pressure. Therefore, the purpose of this study is to examine the combined effects of the two fruits on the lipidemia of alloxan-induced albino rats. Utilizing the glucose dehydrogenase method, glucometer accu-check was used for the evaluation of blood glucose levels. Investigations were also conducted on alloxan-induced diabetic albino rats to measure total cholesterol, triglycerides, high density lipoprotein (HDL), and low density lipoprotein (LDL). According to the results, B. aegyptiaca and A. digitata fruit extracts significantly reduced the lipid profiles of the treated groups when used at concentrations of 80:20, 160:40, and 240:60 mg/Kg body weight, respectively. While the lipid profiles were significantly reduced in groups that received treatment at dosages of 100, 200, and 300 mg/kg body weight. However, the groups treated with the highest doses of the extracts demonstrated the most significant effects on the levels of triglycerides (47mg/dl), HDL (79mg/dl), and LDL (40mg/dl). The fruits have shown cumulative effects on their potential to lower the lipid profile of diabetic rats, validating their folkloric usage in the management of cardiovascular illnesses.